Cerebral Wegener’s Granuloma: Surgery Mandatory for Diagnosis and Treatment - Federico Nicolosi; Giovanni Nodari; Giannantonio Spena; Elena Roca; Karol Migliorati; Giacomo Esposito; Roberto Stefini; Marco Fontanella; Pier Paolo Panciani (Case Reports in Neurological Medicine)
The involvement of the central nervous system in case of Wegener granulomatosis (WG) is infrequent and usually leads to cranial nerve abnormalities, cerebrovascular events, and seizures. Meningeal involvement is quite rare and usually is due to the spreading from adjacent disease in the skull base. We described the case of a remote intraparenchymal Wegener’s granuloma in a 55-year-old man presenting with seizures and a history of severe generalized WG. The radiological findings were not useful for the diagnosis, and the pharmacological treatment was ineffective. The importance of a surgery in case of localized WG has been emphasized, in order to confirm the diagnosis and to avoid additional medicaments, like antiepileptic drugs, potentially harmful in immunosuppressed patients.